Outside the Operating Theatre Anaesthesia (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Modern hospital practice has seen the role of the anaesthesiogist expand beyond the operating theatre complex. While the operating theatres have experienced staff, adequate equipment and monitors, providing anaesthesian outside this complex is challenging and requires expertise and skill.Journal of Bangladesh Society of Anaesthesiologists 2015; 28(1): 32-38